2018 ACM/IEEE 45th Annual International Symposium on Computer Architecture (ISCA) 2018
DOI: 10.1109/isca.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

EVA²: Exploiting Temporal Redundancy in Live Computer Vision

Abstract: Hardware support for deep convolutional neural networks (CNNs) is critical to advanced computer vision in mobile and embedded devices. Current designs, however, accelerate generic CNNs; they do not exploit the unique characteristics of real-time vision. We propose to use the temporal redundancy in natural video to avoid unnecessary computation on most frames. A new algorithm, activation motion compensation, detects changes in the visual input and incrementally updates a previously-computed activation. The tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…Motion-based Algorithms Our ISM algorithm shares a similar key observation as some recent motion-based vision algorithms such as EVA 2 [14] and Euphrates [78], in that correlation across frames in a video stream can be used to simplify continuous vision tasks. Euphrates [78] focuses on computing regions-of-interest (ROIs) in object detection and tracking tasks.…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…Motion-based Algorithms Our ISM algorithm shares a similar key observation as some recent motion-based vision algorithms such as EVA 2 [14] and Euphrates [78], in that correlation across frames in a video stream can be used to simplify continuous vision tasks. Euphrates [78] focuses on computing regions-of-interest (ROIs) in object detection and tracking tasks.…”
Section: Related Workmentioning
confidence: 98%
“…In ASV, the sequencer also chooses key frames. Although complex adaptive schemes are feasible [14,78], we found that a simple strategy to statically set the key-frame window suffices (Sec. 7.2).…”
Section: Hardware Architecturementioning
confidence: 99%
“…Recent work [8,82] demonstrates the utility of simulation frameworks for edge computing on drones; cote is an analogous utility for the orbital edge. Machine inference accelerators [14,15,24,33] could significantly shorten full-coverage CNP pipeline depths, although some that rely on temporal data redundancy [10] may have limited benefit for devices capturing images at the GTFR.…”
Section: Related Workmentioning
confidence: 99%
“…To reduce the frame latency, prior work has mostly focused on improving the performance of the vision computation stage, i.e., the back-end of the vision pipeline. Back-end optimization techniques include designing more efficient vision algorithms (e.g., simplified Deep Neural Network (DNN) models [16,35,52,67], compressing/pruning DNN models [29,31]) andleveraging motion information [10,22,71]. Back-end optimizations are effective when the back-end dominates the frame latency.…”
Section: Limitations Of Optimizing Only Vision Algorithmsmentioning
confidence: 99%